2017
DOI: 10.1159/000456015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an in vitro Coupled Diffusion Mechanism of Lesion Formation within Microcosm Dental Plaque

Abstract: The purpose of this study was to determine whether or not the dual constant-depth film fermenter (dCDFF) is able to produce caries-like enamel lesions and to ascertain further information regarding the performance of this fully functional biological caries model. Conditions were defined by the continuation (CF) or cessation (FF) of a saliva-type growth medium supply during 50-mM sucrose exposures (8 times daily). Hydroxyapatite (n = 3) and bovine enamel (n = 3) substrata were included within e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Other interesting finding of this study was the higher number of typical subsurface lesions produced by the static compared with the semi-dynamic model. This corroborates Owens, et al 21 (2017), who showed semi-dynamic biofilm model induced less evident subsurface layer, while Arthur, et al 22 (2013) found well-defined subsurface lesions for the static model. The flow in semi-dynamic model may have also washed away free calcium and phosphate from biofilm, reducing their availability to precipitate on the lesion surface.…”
Section: Discussionsupporting
confidence: 85%
“…Other interesting finding of this study was the higher number of typical subsurface lesions produced by the static compared with the semi-dynamic model. This corroborates Owens, et al 21 (2017), who showed semi-dynamic biofilm model induced less evident subsurface layer, while Arthur, et al 22 (2013) found well-defined subsurface lesions for the static model. The flow in semi-dynamic model may have also washed away free calcium and phosphate from biofilm, reducing their availability to precipitate on the lesion surface.…”
Section: Discussionsupporting
confidence: 85%
“…In vitro model systems have been previously used to evaluate the effects of various interventions, including triclosan ( 36 38 ), chlorhexidine ( 39 41 ), and enzymes ( 42 ), on dental plaques in vitro and to model caries-like lesions ( 43 ). These approaches have provided useful insights into the mode of action and bacteriological effects of a variety of antiplaque agents within steady-state in vitro plaque systems ( 40 , 44 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…As the use of starch within the CDFF is novel it was decided to use a concentration of 2% to match the sucrose source. Volumes of 2% sucrose and 2% starch were prepared and autoclaved at a lower temperature of 116°C and 1900 mBar to prevent any sugar degradation [ 4 ]. All other equipment including the CDFF units and silicon pipes were autoclaved at 121°C.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, there have been no studies into the cariogenicity of starch using the constant depth film fermenter (CDFF) model system rather than using sucrose exclusively as a means of inducing an acid response by the oral bacteria [ 4 6 ]. By employing two constant depth film fermenters in parallel as a dual setup (dCDFF) [ 5 ] it is possible to directly compare sucrose with starch whilst ensuring all other factors are equal, including artificial saliva sources and inoculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation